Framing a Knowledge Domain Visualization on Green Human Resource Management: A Bibliometric Analysis from 2008-2022 - Noor, Qaisra; Ilyas, Amina; Javaid, Zainab; Khan, Hamayun (Pakistan Journal of Humanities and Social Sciences, 2023)
The green workplace has captured the interest of both academia and business during the last two decades. As a result, new academic disciplines like green human resource management emerged. GHRM can play a significant role in the development of corporate sustainability. This study focuses on comprehending the idea of GHRM and offers a current explanation of GHRM practices. In order to analyze and draw conclusions from 489 publications that were retrieved from Scopus database spanning a time period of almost two decades, the authors used the bibliometric method from 2008-2022. Bibliometric R-package and VOS viewer software are used to draw comprehend conclusions on GHRM scholarship. The study offers some important facts that could help academics and management conceptualize GHRM practices within their individual firms, which are now limited to certain businesses, geographies, developed countries, and HR approaches (hiring, training, and incentive). This effort also provides with the frame of acquaintance on GHRM by classifying various keywords, social erection impact journals, intellectual, conceptual, and reputable writers in this area. The study acts as the starting point for future GHRM research to understand changes in this area during the preceding 14 years. The information has been examined in terms of notable writers, the most read journals, important themes, and a logical and academic organization. The domain is in its early stages of further development, the research claims. Thus, more time-consuming study is needed to contribute to development of a deeper understanding of it developing profession.